2013
DOI: 10.1021/jp403350j
|View full text |Cite
|
Sign up to set email alerts
|

Role of Humidity and Oxygen Level on Damage to DNA Induced by Soft X-rays and Low-Energy Electrons

Abstract: Single- and double-strand breaks induced by soft X-rays (1.5 keV) and photo-emitted LEEs (0-30 eV) were measured in dry and humid thin films of plasmid DNA irradiated under different controllable levels of oxygen at standard ambient temperature and pressure (SATP). values derived from these experiments shows that the presence of HO and changing the atmosphere from N to O, while keeping all other experimental parameters constant, increases the formation of DSBs by factors of 4.5 and 11.8 for X-rays and LEEs, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 67 publications
0
18
0
1
Order By: Relevance
“…LEEs with an average energy of 5.8 eV and a distribution peaking at 1.4 eV could induce DSBs with G values (i.e., yields per energy deposited in DNA) of 8 to 22 nmol/J, which is 1.6 times larger than that of 1.5-keV photons. Applying a similar and improved technique to produce LEEs, Alizadeh et al measured conformational damages from dry, oxygenated, and humid films of DNA, LEE-irradiated under standard atmospheric temperature and pressure (SATP) [99]. Their results were compared with the yields produced by 1.5-keV X-rays.…”
Section: Clustered Dna Damages Induced By Leesmentioning
confidence: 99%
“…LEEs with an average energy of 5.8 eV and a distribution peaking at 1.4 eV could induce DSBs with G values (i.e., yields per energy deposited in DNA) of 8 to 22 nmol/J, which is 1.6 times larger than that of 1.5-keV photons. Applying a similar and improved technique to produce LEEs, Alizadeh et al measured conformational damages from dry, oxygenated, and humid films of DNA, LEE-irradiated under standard atmospheric temperature and pressure (SATP) [99]. Their results were compared with the yields produced by 1.5-keV X-rays.…”
Section: Clustered Dna Damages Induced By Leesmentioning
confidence: 99%
“…Alizadeh and Sanche [146] employed this technique to examine how the presence of several cellular components (such as, O 2 , H 2 O and O 2 /H 2 O) modulates the LEE-induced damage to DNA molecules. They observed that for hydrated DNA films in an oxygenated environment, the additional LEE-induced damage that results from the combination of water and oxygen exhibits a super-additive effect, which produces a yield of DSB almost seven times higher than that obtained by X-ray photons.…”
Section: Lees Interaction and Induced Damage Under Cellular Conditionsmentioning
confidence: 99%
“…32 Table II presents dry DNA, this ratio is 2.5, which corresponds to tightly bound water molecules attached to the phosphate group that cannot be removed by vacuum desiccation. 49,50 Assuming a nucleosome as a cylinder with diameter and height of 10 and 6 nm, respectively, the absorbed dose in the nucleosome is 2.6 kGy, which is 2 orders of magnitude smaller than that in the DNA, owing to the smaller mass of DNA relative to that of nucleosome. However, the dose of 2.6 kGy is still much higher, by 2 or 3 orders of magnitude, than those currently administered in the clinic for macroscopic volumes.…”
Section: A Absorbed Dose In Dna By Auger Electrons Of 5-18 Evmentioning
confidence: 99%